Effect of iron ... zinc fortified milk on iron status and functional outcomes in underweight children - Endang Dewi Lestari; Saptawati Bardosono; Leilani Lestarina; Harsono Salimo (Indonesian Pediatric Society, 2009)
Background Iron and zinc are essential micronutrients duringschool-age period. Milk could be an alternative medium formineral fortification because it is consumed frequently bychildren.Objective To evaluate the effect of iron-zinc fortified milksupplementation on iron status and functional outcomes inunderweight children.Methods 44 2 underweight subjects aged 7-10 years attending 10primary schools in Jakarta and Solo were recruited in the study.Subjects who had chronic illnesses, severe anemia, thalassemiaor cow's milk allergy were excluded. Blood samples were analyzedto determine hemoglobin, serum ferritin and serum zinc. SerumCRP was measured in sub sampled subjects (n= 60). Subjectswere randomizedly allocated to receive iron-zinc fortified milk(n = 225) and standard milk (n = 217) for six months. The fortifiedmilk will provide additional6.3 mg iron and 1.5 mg zinc per day (2feeds). The main outcomes measured were iron status, cognitivefunction, growth, physical fitness and morbidity.Results Study groups were comparable at baseline. The fortifiedmilk group had better physical fitness score and exercise durationat baseline. Both milk supplementations reduced the prevalenceof anemia and iron deficiency. Fortified milk improved the speedprocessing score (P< 0.0001), height (P<0.0001) and sittingheight (P=O.Ol) significantly.Conclusion Supplementation of milk reduces the prevalence ofanemia and iron deficiency. Zinc-iron fortified milk gives positiveimpact on cognitive performance, growth, and physical fitness.